The peripheral chimerism of bone marrow–derived stem cells after transplantation: regeneration of gastrointestinal tissues in lethally irradiated mice. Issue 5 (20th January 2014) - Filip, Stanislav; Mokrý, Jaroslav; Vávrová, Jiřina; Šinkorová, Zuzana; Mičuda, Stanislav; Šponer, Pavel; Filipová, Alžběta; Hrebíková, Hana; Dayanithi, Govindan
Abstract Bone marrow–derived cells represent a heterogeneous cell population containing haematopoietic stem and progenitor cells. These cells have been identified as potential candidates for use in cell therapy for the regeneration of damaged tissues caused by trauma, degenerative diseases, ischaemia and inflammation or cancer treatment. In our study, we examined a model using whole‐body irradiation and the transplantation of bone marrow (BM) or haematopoietic stem cells (HSCs) to study the repair of haematopoiesis, extramedullary haematopoiesis and the migration of green fluorescent protein (GFP+) transplanted cells into non‐haematopoietic tissues. We investigated the repair of damage to the BM, peripheral blood, spleen and thymus and assessed the ability of this treatment to induce the entry of BM cells or GFP+lin−Sca‐1+ cells into non‐haematopoietic tissues. The transplantation of BM cells or GFP+lin−Sca‐1+ cells from GFP transgenic mice successfully repopulated haematopoiesis and the haematopoietic niche in haematopoietic tissues, specifically the BM, spleen and thymus. The transplanted GFP+ cells also entered the gastrointestinal tract (GIT) following whole‐body irradiation. Our results demonstrate that whole‐body irradiation does not significantly alter the integrity of tissues such as those in the small intestine and liver. Whole‐body irradiation also induced myeloablation and chimerism in tissues, and induced the entry of transplanted cells into the small intestine and liver. This result demonstrates that grafted BM cells or GFP+lin−Sca‐1+ cells are not transient in the GIT. Thus, these transplanted cells could be used for the long‐term treatment of various pathologies or as a one‐time treatment option if myeloablation‐induced chimerism alone is not sufficient to induce the entry of transplanted cells into non‐haematopoietic tissues.